2008
DOI: 10.1111/j.1600-0501.2007.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of quality of life of elderly with mandibular implant‐supported fixed prostheses

Abstract: Treatment with implant-supported fixed prostheses improved QL in the elderly; these effects are better detected by specific instruments focused on the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
61
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 18 publications
13
61
0
5
Order By: Relevance
“…In the present study, OHIP questionnaire was utilized to screen transition of the attributable to its affectability to recognize the effect of prosthodontic therapy and its extensive usage (27). …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, OHIP questionnaire was utilized to screen transition of the attributable to its affectability to recognize the effect of prosthodontic therapy and its extensive usage (27). …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Nonetheless, there are few studies assessing the Oral Health-Related Quality of Life (OHRQoL) of implant prosthesis wearers. [3][4][5][6] Although different generic scales have been used, 3,4,[7][8][9] specific questionnaires are preferred to measure the impact of implant prostheses on the OHRQoL. 5,6 In this respect, a new, short and precise index, called 'Quality of Life with ImplantProstheses (QoLIP-10)' 5,6 has recently been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] However, some studies reported that patients with mandibular implant supported overdenture had similar impacts on quality of life and satisfaction with treatment when compared with conventional lower complete dentures. 12 Furthermore, no differences in quality of life and satisfaction are present when conventional maxillary complete dentures were compared with maxillary implant supported dentures.…”
Section: Introductionmentioning
confidence: 99%